2017
DOI: 10.3389/fvets.2017.00063
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequence Analysis of Antimicrobial Resistance Genes in Streptococcus uberis and Streptococcus dysgalactiae Isolates from Canadian Dairy Herds

Abstract: The objectives of this study are to determine the occurrence of antimicrobial resistance (AMR) genes using whole-genome sequence (WGS) of Streptococcus uberis (S. uberis) and Streptococcus dysgalactiae (S. dysgalactiae) isolates, recovered from dairy cows in the Canadian Maritime Provinces. A secondary objective included the exploration of the association between phenotypic AMR and the genomic characteristics (genome size, guanine–cytosine content, and occurrence of unique gene sequences). Initially, 91 isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 75 publications
(102 reference statements)
2
39
0
Order By: Relevance
“…The bla TEM-68 variant probably evolved from bla TEM-47 , and both are not very frequent in Poland. Outside this area, there was a report from Canada, where bla TEM-47 was found in Streptococcus dysgalactiae (Vélez et al 2017). To the best of our knowledge, this study reports the first isolate carrying a bla TEM-47/68 variant found outside the clinical setting in Poland.…”
Section: Resultsmentioning
confidence: 72%
“…The bla TEM-68 variant probably evolved from bla TEM-47 , and both are not very frequent in Poland. Outside this area, there was a report from Canada, where bla TEM-47 was found in Streptococcus dysgalactiae (Vélez et al 2017). To the best of our knowledge, this study reports the first isolate carrying a bla TEM-47/68 variant found outside the clinical setting in Poland.…”
Section: Resultsmentioning
confidence: 72%
“…In fact, pyogenic streptococci have been recognized as non-β-lactamase-producing bacteria, where resistance to β-lactams is essentially mediated by alterations to the binding site of penicillin-binding proteins (PBPs) ( Vannice et al, 2019 ). Nevertheless, a recent study based on whole-genome sequencing revealed the presence of β-lactamases determinants of S. uberis and SDSD isolates bovine mastitis ( Vélez et al, 2017 ). Still, there is a need for actional studies to assess the potential of these β-lactamases, and the role of these species as a reservoir of determinants of resistance.…”
Section: Antibiotics and Mechanisms Of Resistancementioning
confidence: 99%
“…Resistance to tetracyclines (TET) among streptococci strains is often found in high rates ( Nakamur et al, 2011 ; Emaneini et al, 2014 ; Gherardi et al, 2014 ; Vélez et al, 2017 ; Gizachew et al, 2019 ). In streptococci, genes encoding resistance to TET are frequently acquired by MGEs, which also harbor erythromycin resistance determinants ( Brenciani et al, 2004 , 2007 , 2011 ; Emaneini et al, 2014 ; Cattoir, 2016 ).…”
Section: Antibiotics and Mechanisms Of Resistancementioning
confidence: 99%
“…Opportunistic infection of the bovine mammary gland by S. uberis can lead to the bacterium acting as a major pathogen, causing the inflammatory disease mastitis ( 3 ). Economic losses associated with bovine mastitis have been estimated at $35 billion per year globally, with S. uberis being the leading cause of bovine mastitis in New Zealand ( 4 ) and the United Kingdom ( 5 ) and a major cause in the Unites States ( 6 ), Canada ( 7 ), and Chile ( 8 ), among other countries.…”
Section: Genome Announcementmentioning
confidence: 99%